The Dark Crystal, Age of Resistance: The Quest / For the Dual Glaive - Book 4 Age of resistance. - Addiss, Jeff; Matthews, Will; Andelfinger, Nicole; Basla, Matias; Cristobal, Esdras, 1979-; Muerto, Miquel; Fernandes, Rod; Campbell, Jim (Letterer); Henson, Jim; Jim Henson Company (Los Angeles, California : Archaia, 2020)
"Thirty trine before the Age of Resistance, the Arathim Wars are in full swing. To save her village, the Stonewood Maudra sends her greatest warrior, Ordon, to the Tomb of Relics to retrieve a mythical weapon that promises to turn the tide of the war. But when he meets young Fara, the two must find a way to work together to retrieve a legendary weapon--The Dual Glaive--before their village is destroyed by the deadly Arathim.--Provided by publisher.
Keywords: Elves -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Elves -- Fiction; Quests (Expeditions) -- Fiction; Imaginary wars and battles -- Fiction; Fantasy comics; Graphic novels